Knowledge and Benefits availed by Members of Self Help Groups - V. V. Waghmare,; R.P. Kadam, (Journal of Agricultural Extension Management, 2025)
The Self Help Group acts as a strong cohesive force for bringing about socio-economic development of weaker sections of the community. This paper studies the personal and socio-economic characteristics of beneficiary women of Self Help Groups; knowledge level of beneficiary 1vo111en about activities of Self-Help Groups and benefits availed by women members